2016
DOI: 10.1177/0255761415590361
|View full text |Cite
|
Sign up to set email alerts
|

Towards the future: Teachers’ vision of professional development in the arts

Abstract: Teachers enrolled in a professional development program involving artists on site at cultural institutions participated in a study in which they expressed their views on upgrading in the arts. Findings indicate that they were influenced in their own schooling by passionate teachers who conveyed the importance of the arts. Their progress was impeded by a self-perception of their own limited artistic ability. Community experiences, such as private lessons and amateur productions, played a more significant role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
5
0
3
Order By: Relevance
“…This approach to improving provision can be contrasted with other schools from the wider sample, who had attempted to “buy in” specialist support in order to improve standards in the subject. Although research has shown such strategies offer great potential if productive partnerships develop (Andrews, 2016; Bremner, 2013; Jeanneret & Stevens-Ballenger, 2013; Luebke, 2013), the schools that had attempted this in the current study experienced considerable difficulties in sustaining any positive impact. In relation to their expectancy for success in their own teaching, for instance, the teachers observed the specialists deliver music in a way which they never imagined they could replicate.…”
Section: Findings and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This approach to improving provision can be contrasted with other schools from the wider sample, who had attempted to “buy in” specialist support in order to improve standards in the subject. Although research has shown such strategies offer great potential if productive partnerships develop (Andrews, 2016; Bremner, 2013; Jeanneret & Stevens-Ballenger, 2013; Luebke, 2013), the schools that had attempted this in the current study experienced considerable difficulties in sustaining any positive impact. In relation to their expectancy for success in their own teaching, for instance, the teachers observed the specialists deliver music in a way which they never imagined they could replicate.…”
Section: Findings and Discussionmentioning
confidence: 92%
“…Recent research has suggested that partnerships with specialist teachers represent a way of managing the issue, whereby an external champion or specialist could work alongside a school to support their delivery of music (Andrews, 2016; Jeanneret & Stevens-Ballenger, 2013; Luebke, 2013). The findings from this case study build upon this work by demonstrating the benefits of situating ownership of the programme with the teachers themselves, illustrating how this might be enacted in practice.…”
Section: Conclusion and Cautionsmentioning
confidence: 99%
“…Desde hace años, algunas instituciones de educación artística tienen convenios con escuelas de primaria y secundaria (inspirándose en las magnet schools) para enviar profesorado artista a las aulas de primaria y secundaria, con el fin de motivar e inspirar procesos creativos y trabajar con el profesorado especialista y generalista de dichos centros. Dichas iniciativas suelen estar sujetas a la financiación de Ayuntamientos y hasta ahora cuentan con muy buenos resultados, participando centenares de estudiantes y un número elevado de artistas «residentes» (Andrews, 2016).…”
Section: Tener Maestros Especialistas En Música Y Arte Nos Hace «Más Europeos»unclassified
“…Over the past four decades, and particularly since the 1978 survey of primary education in England, carried out by HMIs of Schools, there has been much discussion about the teaching of music in primary schools, and the challenges it presents (HMI 1978;Mills 1989;Bresler 1993 andCollins 2014;). More than many other curriculum subjects, music is generally perceived by teachers and STs alike as one requiring 'special skills', such as being proficient at playing a musical instrument (HMI 1978;Mills 1991;Glover and Ward 1993;Stunell 2010;Andrews 2016). Evidence suggests that STs perceive, along with serving teachers, that there is a need to have formal training in order to teach music (Hennessy 2000;Wiggins and Wiggins 2008), and that musical ability is fixed, or only given to a chosen few (Hennessy 2000;Biasutti, Hennessy and Vugt-Jansen 2014).…”
Section: Music In the Primary Schoolmentioning
confidence: 99%